2021
DOI: 10.1215/00703370-8977691
|View full text |Cite
|
Sign up to set email alerts
|

Pain Trends Among American Adults, 2002–2018: Patterns, Disparities, and Correlates

Abstract: Determining long-term trends in chronic pain prevalence is critical for evaluating and shaping U.S. health policies, but little research has examined such trends. This study (1) provides estimates of pain trends among U.S. adults across major population groups; (2) tests whether sociodemographic disparities in pain have widened or narrowed over time; and (3) examines socioeconomic, behavioral, psychological, and medical correlates of pain trends. Regression and decomposition analyses of joint, low back, neck, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 91 publications
6
96
1
Order By: Relevance
“…Finally, we attend to the fact that the analyses above include all ages 18 and older. Age has a major impact on pain levels [16], as well as the distribution of most pain covariates [55].…”
Section: Approachmentioning
confidence: 99%
“…Finally, we attend to the fact that the analyses above include all ages 18 and older. Age has a major impact on pain levels [16], as well as the distribution of most pain covariates [55].…”
Section: Approachmentioning
confidence: 99%
“…NASEM (2021) reviewed several studies that found rising levels of pain in the US. These include our 2015 paper, which documented increases in a range of specific pains (listed in the introduction), as well as Nahin et al (2019) who used the Medical Expenditure Panel Survey (MEPS) to find that the proportion of adults reporting painful health conditions increased from 32.9 percent in 1997-98 to 41.0 percent in 2013-14, andZajacova et al (2021) who find "a large escalation in pain prevalence among adults" (NASEM, 2021(NASEM, , p. 254) from 1997(NASEM, -98 to 2013 in the National Health Interview Survey (NHIS). Zimmer & Zajacova (2020) also document "the increasing pain prevalence in older Americans" from 1992 to 2014 in the Health and Retirement Study (HRS).…”
Section: Rising Despair Rising Pain and Deteriorating Mental Healthmentioning
confidence: 99%
“…The finding that this boom is unbalanced has relevant implications. First, people with less education have poorer health and fewer financial resources, and cycling could help with both, but the opposite is taking place, because the educational gap in cycling is large and increasing (Hendi, 2017;Mäki, Martikainen, Eikemo, Menvielle, & Lundberg, 2013;Zajacova, Grol-Prokopczyk, & Zimmer, 2021).…”
Section: Discussionmentioning
confidence: 99%